2005
DOI: 10.1007/s00421-005-1353-0
|View full text |Cite
|
Sign up to set email alerts
|

Pure eccentric exercise does not activate blood coagulation

Abstract: Eccentric exercise can cause skeletal muscle damage with ultrastructural disruption, inflammation and increased proteolytic enzyme activity. It may be possible that these changes are able to trigger blood coagulation in vivo. The aim of the study was to investigate changes in blood coagulation via the measurement of aPTT, the thrombin potential (total [TTP] and endogenous [ETP], both intrinsic [in] and extrinsic [ex]) and the thrombin generation (prothrombinfragment 1 + 2 [F1 + 2] and thrombin-antithrombin com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Exercise-induced thrombin generation seems to be a complex function of exercise type (Hilberg et al, 2005), intensity (Weiss et al, 1998) and duration (Mockel et al, 2001;Hilberg et al, 2003b). It has been considered that metabolic and ⁄ or adrenergic factors play some roles in exercise-induced thrombin generation, though the precise mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise-induced thrombin generation seems to be a complex function of exercise type (Hilberg et al, 2005), intensity (Weiss et al, 1998) and duration (Mockel et al, 2001;Hilberg et al, 2003b). It has been considered that metabolic and ⁄ or adrenergic factors play some roles in exercise-induced thrombin generation, though the precise mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise‐induced thrombin generation seems to be a complex function of exercise type (Hilberg et al. , 2005), intensity (Weiss et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the aerobic or anaerobic exercise have the same effect on the aPTT time and both of them led to a significant decrease in aPTT volatile and rise above the level of the ground state, is in a recovery. Hilberg et al [13] showed aPTT time to jump from a height of 55 cm deep extroverted than 90 minutes of exercise at 90% lactate threshold is much less reduced on a stationary bicycle pedal stronger stimulus to increase Thrombin is potential. Menzel and Hilberg [5] aPTT significant shortening of average activity with 80% of the anaerobic threshold in young men and the elderly were fixed.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown that strenuous exercise leads to a shortening of the activated partial thromboplastin time, and results in an increase of thrombin generation markers (Hilberg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%